Strengthening Healthy Food Literacy through Education and Culinary Demonstrations of Nutrient-Dense Scrambled Eggs and Fish Nuggets - Eva Amalia; Heri Nuryanto; Miratia Afriani; Agung Arif Gunawan; Muhammad Syauqan Rizieq; Eko Lamendri; Egi Dio Aprilian (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
The implementation of Indonesia’s Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) in elementary schools faces a significant challenge in the form of food waste, particularly from vegetable and fish-based menu components. This community service program was conducted at SD Negeri 011 Sekupang, Batam, to strengthen healthy food literacy among students and improve acceptance of nutritious foods through an integrated educational and culinary intervention. The program was considered important because nutritional literacy is a key determinant of healthy eating behavior and directly influences the effectiveness of school feeding programs. The intervention combined visual education on the “Isi Piringku” (My Plate) balanced nutrition guidelines with interactive culinary demonstrations using a Functional Gastronomy approach. Students participated in educational sessions, discussions, sensory evaluations, and demonstrations of Homemade Healthy Fish Nuggets and Nutrient-Dense Vegetable Scrambled Eggs prepared from locally available ingredients. Program effectiveness was measured through pre-test and post-test questionnaires, plate-waste observations, and organoleptic evaluations. The results revealed a substantial improvement in students’ nutritional knowledge, with average scores increasing by 96.02% from pre-test to post-test. Furthermore, 95% of participating students consumed the modified food products completely, indicating a significant enhancement in sensory acceptance. The findings demonstrate that combining nutrition literacy with sensory-oriented culinary innovation can effectively reduce food refusal and encourage healthier eating behaviors among children. This approach offers a practical model for optimizing the impact of the MBG program while supporting the development of sustainable healthy eating habits in school communities.